Pengelompokan Tahapan Pembuatan Tudung dengan Efektif dan Efisien Guna Membangun Perekonomian Masyarakat Rentan Miskin di Desa Grujugan - Asep Supriyanto; Sri Wahyuningsih; Asni Tafrikhatin; Wijaya; Arba'i Yusuf; Uyun Fatmawati; Agam Kethoet Casmara; Anggi Dwi Alifah; Apriliana Pratiwi; Bagas Mei Saputra; Dwi Rahayu; Isma Yoha Hafur; Mei Purwaningsih; Rizka Cahyo; Wisnu Pajar Riangga (Politeknik Piksi Ganesha Indonesia, 2022)
Grujugan Village, Petanahan, Kebumen is one of the villages where 90% of the people have their main livelihood. The manufacturing process is carried out independently and manually from the initial process of cutting bamboo to finishing the product. The program or activity of efficiency in making hoods from woven bamboo consists of preparation, observation, preparation of tools and materials. Providing tool assistance makes the production process faster and more efficient than the manual production process. It is proven that the production of woven bamboo hoods is more than manual. The community empowerment program (P2MD) is expected to improve the economic sector in Grujugan village.